The Impact of Stair and Squat Jump Training on Men's Volleyball Smash Results - Nyoman Sukrawan; Rahmah Rahmah; Sardiman Sardiman (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study aimed to investigate whether climbing stairs and squat jump training had an impact on smash results, and also to determine which of these two training methods was more effective for improving smash results. The study focused on the men's volleyball team at SMA Negeri 1 Dampal Selatan. Materials and methods. This is an experimental research that follows the Two-Group Pretest-Posttest Design. The volleyball smash test was used as the instrument for this research. The research was conducted on 12 members of the Men's Volleyball Team at SMA Negeri 1 Dampal Selatan. The data analysis technique used for this research was the t-test. Results. According to the t-test results for the Up and Down Stairs exercise, it is evident that the t count (6.318) is greater than the t -able (1.795). Similarly, for the Squat Jump exercise, the t-test results indicate that the t-count (5.085) is greater than the t-table (1.795). The percentage results show that the improvement in Smash ability was 13.76% with climbing and descending stairs training and 14.31% with Squat Jump training. Conclusion. After analyzing the percentage increase, the results suggest that Squat Jump training is a more effective method for enhancing Smash results in the volleyball game for the men's team at SMA Negeri 1 Dampal Selatan. This implies that incorporating Squat Jump training into the team's regular training routine may lead to better Smash outcomes during the game.